Strategic analysis and growth in an emerging economy (B) : developing competitive advantage - mobile handset companies' generic and multinational strategies in India - Salwan, Prashant (London : NeilsonJournals Publishing, 2009)
This is the second case in the series on strategic analysis and growth in an emerging economy. In this case the mobile handset manufactures have to decide which competitive strategies to adopt. India's market is attractive as manufacturing inside India has become very cost effective. The competitors have to have market specific and country specific strategies. The major players(Nokia, Samsung, and Sony Ericsson) have differing resources and competitive strengths. They have to develop competitive generic strategies for India and develop multinational strategies for cost leadership, linking the advantages of Indian manufacture with their global market positions.
Originally Published InSalwan, P. (2009). Strategic analysis and growth in an emerging economy (B): Developing competitive advantage -- mobile handset companies' generic and multinational strategies in India. Journal of International Business Education, 4(1), 87-102. JIBE4-0CS4B.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nokia (Firm) -- Case studies; Cell phone services industry -- India -- Case studies; Competition -- India -- Case studies; India -- Economic conditions -- 1991- -- Case studies